Penerapan Sistem Informasi Mobile JKN BPJS Untuk Meningkatkan Akses Dan Kualitas Layanan Kesehatan - Putri; Rina; Yeni, Hari (CV. SINAR HOWUHOWU, 2026)
The use of information technology in the health sector is increasingly seen as a strategic step to improve the quality of public services. One effort is the development of the Mobile JKN application by BPJS Kesehatan, which is intended to facilitate National Health Insurance (JKN) participants in accessing health services. This study aims to examine how the implementation of the Mobile JKN application contributes to improving access and qualit. of health services for participants. The approach used is descriptive qualitative, with data collection techniques consisting of a literature review, direct observation of application usage, and limited interviews with Mobile JKN users. The results show that Mobile JKN plays an important role in supporting the digital transformation of health services, but still requires continuous system development and increased education for users. The Mobile JKN application helps participants in obtaining services more easily and efficiently, while increasing the transparency of information related to membership and health services. However, the use of this application still faces several obstacles, including limited digital literacy of users, uneven internet network quality, and technical problems in the application system. Based on these findings, this study concludes that Mobile JKN plays an important role in supporting the digital transformation of health services, but still requires continuous system development and increased education for users. The Mobile JKN application helps participants in obtaining services more easily and efficiently, while increasing the transparency of information related to health membership and services. However, the use of this application still faces several obstacles, including limited digital literacy of users, uneven internet network quality, and technical problems in the application system. Based on these findings, this study.